AN ANALYSIS OF ENGLISH WRITING ERRORS IN EFL LEARNERS’ RECOUNT TEXT - Alisa Maulida Sari; Rahma Ayuditya Putri; Aldha Williyan (PRODI PENDIDIKAN BAHASA INGGRIS INSTITUT PENDIDIKAN DAN BAHASA INVADA, 2023)
This research discusses the analysis of students' errors in writing recount texts. This study aims to analyze the types of errors made by undergraduate students’ writing scores at the English Language Teaching Department at one of the universities in Cirebon. This study focuses on writing errors taken from three categories of English proficiency levels (low, average, high). This study used the descriptive qualitative method. There were six participants. The data were taken from their recount text writing results. The results of this study show that there are four types of errors based on Surface Strategy Taxonomy by students: Omission, Addition, Misinformation, and Misordering. The result of the total number of student errors is 37 which contains 14 Omission (37.83%), three Addition (8.11%), 19 Misinformation (51.36%), and one Misordering (2.70%). The most errors were made by Misinformation, with 19 errors (51.36%). It can be concluded that the ability of undergraduate students at one university in Cirebon is still low in writing recount text.